Occurrence, Chronicity and Intensity of Itch in a Clinical Consecutive Sample of Patients with Skin Diseases: A Multi-centre Study in 13 European Countries - Christina Schut; Florence J. Dalgard; Jon Anders Halvorsen; Uwe Gieler; Lars Lien; Lucía Tomas Aragones; Françoise Poot; Gregor B. E. Jemec; Laurent Misery; Lajos Kemény; Francesca Sampogna; Henriët van Middendorp; et al. (Medical Journals Sweden, 2018)
Itch is an unpleasant symptom, affecting many dermatological patients. Studies investigating the occurrence and intensity of itch in dermatological patients often focus on a single skin disease and omit a control group with healthy skin. The aim of this multi-centre study was to assess the occurrence, chronicity and intensity (visual analogue scale 0-10) of itch in patients with different skin diseases and healthy-skin controls. Out of 3,530 dermatological patients, 54.3% reported itch (mean ± standard deviation itch intensity 5.5 ± 2.5), while out of 1,094 healthy-skin controls 8% had itch (3.6 ± 2.3). Chronic itch was reported by 36.9% of the patients and 4.7% of the healthy-skin controls. Itch was most frequent (occurrence rates higher than 80%) in patients with unclassified pruritus, prurigo and related conditions, atopic dermatitis and hand eczema. However, many patients with psychodermatological conditions and naevi also reported itch (occurrence rates higher than 19%).